THE GENUS VATICA L. (DIPTEROCARPACEAE) IN CEYLON - a. j. g. h. kostermans (Reinwardtia, 1982)
In Ceylon 4 endemic species of Vatica occur of which one. (Vatica obscura) occurs as a riverine species in the dry zone, the other three are restricted to the wet zone, two of them on well drained soils, one (V. paludosa) in marshy places. Vatica lewisiana is removed from CotyleloHuni and again asigned to Vatica. Vatica, paludosa Kosterm., sp. nov. is neither identical with V. roxburghiana, an Indian species, nor the same as V. chinensis L., a species of unknown origin, to which the Ceylonese material has been referred formerly.